Detection of Mercury Residue in Aquatic Products Using Direct Sampling - Tu, Hai; Liu, Tiebing; Chun, Mei; Zhu, Yinbang; Wang, Jiasheng (Asian Journal of Chemistry, 2015)
The method was developed for rapid detection of mercury residue in aquatic products using direct sampling. Chemical pretreatment like digestion was not necessary in this method, but only simple pretreatment by physical way is needed. The results showed that the limit of detection was 6.3 μg kg-1, rate of recovery was 95-105 %, linearly dependent coefficient is 0.9995 and the relative standard deviation of detected precision was 5.01-6.77 %, while the relative deviation compared with standard value of precision is 0.397 %. With the advantages of safety, convenience, environment-protection, accuracy, high precision and low limit of detection, the method is obviously advantage compared with microwave digestion- atomic fluorescence spectrometry and micro digestion-inductive coupled plasma mass spectrometry.